Thecoperitoneal Shunt Migration through Anus–A Rare Presentation - Ambekar, Sudheer; Vekariya, Mayank (Indian Journal of Neurosurgery, 2020)
The thecoperitoneal (TP) shunt is a cerebrospinal fluid (CSF) diversion technique. It is a commonly used technique in many neurosurgical conditions, and many complications are associated with it. This is a case of TP shunt migration through the anus. It is an uncommon and rare presentation of one of the complications associated with the TP shunt. Caregivers should keep this in mind about this complication, as it leads to devastating complications like meningitis and suffering for the patient.
Keywords: thecal sac; cerebrospinal fluid; complications